“Through Love’s Arms the Man Can Fly in Every Corner [of Creation]”. Love of God and Love of Neighbors in John the Solitary’s Letters - Pavan, Marco; Poiani, Matteo (Vox Patrum, 2026)
The present contribution offers a first critical edition of a short text ascribed to John the Solitary, named “Letter on love” and witnessed in one 6th century manuscript (BL Add 17169, ff. 124v-126r). This text uses a vocabulary and imagery that can be found in other works of the Johannine corpus, and, therefore, can be ascribed to the same author. The letter is addressed to unnamed ascetics, living in a monastery, and describes love as the main goal of ascetic life. Through love, the monk may attain the full knowledge of the mystery of God and receive the crown of victory and the beautiful garments in the “last day”. The commentary on the letter shows how this short text summarizes some of the key terms and images associated with love in the Johannine corpus.